2018
DOI: 10.5897/jphe2018.1020
|View full text |Cite
|
Sign up to set email alerts
|

Health problems related to algal bloom among seaweed farmers in coastal areas of Tanzania

Abstract: There is a scarcity of research-based data on the factors associated with skin irritation due to algal blooms in seaweed farming. Changes in temperature with an increase in nutrients levels lead to the growth of harmful algal blooms, which produce many active metabolites, some of which induce toxic responses in human including skin irritation. The objective of this study was to identify health problems experienced by seaweed farmers and the seasons when they occur, and how these are treated. A crosssectional s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…Often aquaculture and seaweed operations occur in remote environments, making access to health services challenging (Cavalli et al 2019). Although literature on hazards in seaweed production are scarce and focused on studies carried out in the largest producing regions (see e.g., Said et al 2018;Ngajilo and Jeebhay 2019;Thamrin et al 2019;Thamrin et al 2020;Ngajilo et al 2023;Valderrama et al 2013), it is agreed that cultivation can entail biological (Cavalli et al 2019), ergonomic (Hussin and Khoso 2021;Shimada et al 1990;Thamrin et al 2020), and physical hazards (Hussin and Khoso 2021;Thamrin et al 2019). Thamrin et al (2020), also found that two-thirds (67%) of seaweed workers surveyed suffered from fatigue, especially during busy periods, suggesting that work organisation may also give rise to significant risks.…”
Section: The Industrymentioning
confidence: 99%
“…Often aquaculture and seaweed operations occur in remote environments, making access to health services challenging (Cavalli et al 2019). Although literature on hazards in seaweed production are scarce and focused on studies carried out in the largest producing regions (see e.g., Said et al 2018;Ngajilo and Jeebhay 2019;Thamrin et al 2019;Thamrin et al 2020;Ngajilo et al 2023;Valderrama et al 2013), it is agreed that cultivation can entail biological (Cavalli et al 2019), ergonomic (Hussin and Khoso 2021;Shimada et al 1990;Thamrin et al 2020), and physical hazards (Hussin and Khoso 2021;Thamrin et al 2019). Thamrin et al (2020), also found that two-thirds (67%) of seaweed workers surveyed suffered from fatigue, especially during busy periods, suggesting that work organisation may also give rise to significant risks.…”
Section: The Industrymentioning
confidence: 99%
“…[89,94,138]). However, the physical demands of seaweed farming can be detrimental to the well-being of practitioners; a range of ailments have been reported including musculoskeletal pains from hard physical labour, exposure to marine parasites during tending, and respiratory problems from the off-gassing of vapours during the drying process [90,95,100,[139][140][141]. Similarly, for some, seaweed farming has allowed a reliable income source; creating more consistent quality seaweeds relative to wild collection and safer production in the face of harmful algal blooms compared to fisheries sectors [142].…”
Section: Plos Sustainability and Transformationmentioning
confidence: 99%
“…For example, health effects are also perceived to be connected to low water quality by farmers [ 20 ]. With algal blooms, there are already reported cases [ 21 ]. A study in Ukerewe, an island in Lake Victoria, evidenced the health impacts of cyanobacteria-contaminated drinking water in the area [ 22 ].…”
Section: Introductionmentioning
confidence: 99%